2011
DOI: 10.1007/s00421-011-2220-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 5-h hilly running on ankle plantar and dorsal flexor force and fatigability

Abstract: This study aimed to examine the effects of a 5-h hilly run on ankle plantar (PF) and dorsal flexor (DF) force and fatigability. It was hypothesised that DF fatigue/fatigability would be greater than PF fatigue/fatigability. Eight male trail long distance runners (42.5 ± 5.9 years) were tested for ankle PF and DF maximal voluntary isokinetic contraction strength and fatigue resistance tests (percent decrement score), maximal voluntary and electrically evoked isometric contraction strength before and after the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…In our study, it appears that the specificities of this mountain race (large uphill/downhill sections; unstable ground) led to greater muscle fatigue of the ankle plantar than the dorsi-flexor muscles and the hip adductors and abductors. These data are consistent with the observations made by Fourchet et al, who reported greater ankle plantar than dorsi-flexor strength loss after a 5-h hilly run [55].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, it appears that the specificities of this mountain race (large uphill/downhill sections; unstable ground) led to greater muscle fatigue of the ankle plantar than the dorsi-flexor muscles and the hip adductors and abductors. These data are consistent with the observations made by Fourchet et al, who reported greater ankle plantar than dorsi-flexor strength loss after a 5-h hilly run [55].…”
Section: Discussionsupporting
confidence: 93%
“…During MUM, great fatigue of the plantar flexors has been reported, whereas in dorsi-flexors [31], [47], [55], the magnitude of fatigue appears less [55]. This increased fatigue-induced strength imbalance likely influences the control of AP movements.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these results were not different when calculated over the first 30 contractions only (plantar flexors: 29.7%, P ¼ .04, power ¼ 0.49, ES ¼ 1.09; dorsiflexors: 17.3%, P ¼ .16, power ¼ 0.17, ES ¼ 0.64), as recommended, 10 versus the values we calculated over 50 contractions. These changes affecting only the plantar flexors are in line with previous studies in which the plantar flexors of adults were subjected to fatigue after prolonged 29,30 or shorter-term (ie, 13minute) running. 1 As suggested, 5 one may assume that, to manage fatigued conditions at such a high running speed, the participants unconsciously engaged a midfoot landing strategy, which consequently altered the loading demands on the plantar flexors.…”
Section: Discussionsupporting
confidence: 82%
“…Since the work performed at the ankle is substantial in uphill running (Roberts & Belliveau, ), increasing PF fatigue/damage in downhill sections will likely affect performance in the subsequent uphill sections. Furthermore, trail running may mainly cause greater alterations of muscle function in PF than in dorsiflexors, as previously observed after a 5‐h hilly run (Fourchet et al., ).…”
Section: Discussionsupporting
confidence: 55%
“…Since the work performed at the ankle is substantial in uphill running (Roberts & Belliveau, 2005), increasing PF fatigue/damage in downhill sections will likely affect performance in the subsequent uphill sections. Furthermore, trail running may mainly cause greater alterations of muscle function in PF than in dorsiflexors, as previously observed after a 5-h hilly run (Fourchet et al, 2011). The lower VL activity observed with anterior patterns may result from less pronounced knee extension at initial contact which may decrease VL pre-activation (Shih et al, 2013) and/or from a lower negative work developed by KE muscles during the braking phase (Hamill et al, 2014).…”
Section: Discussionmentioning
confidence: 74%